Design Approaches to Improve Organic Solar Cells - Muhammad, Fahmi Fariq (Journal of Technology Innovations in Renewable Energy, 2023)
Organic solar cells (OSC)s are valuable economical and environmental friendly devices capable to generate electricity from sunlight. This is because of their simple fabrication process and minimal material usage in comparison to the inorganic solar cells. OSCs have not been widely commercialized yet because of their relatively low power conversion efficiency and stability problem. It is expected that these obstacles will be surmounted in a foreseeable future upon rigorous research studies performed in the field. This paper is devoted to reviewing the design related strategies that can be taken to enhance OSC performance. These strategies can be accomplished through modulating the architecture of the devices and by considering the alignment of the molecular energy levels between their active layer components.